Monoclonal Antibodies - Christian Klein (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Monoclonal antibodies are established in clinical practice for the treatment of cancer, and autoimmune and infectious diseases. The first generation of antibodies has been dominated by classical IgG antibodies, however, in the last decade, the field has advanced, and, nowadays, a large proportion of antibodies in development have been engineered. This Special Issue on "Monoclonal Antibodies" includes original manuscripts and reviews covering various aspects related to the discovery, analytical characterization, manufacturing and development of therapeutic and engineered antibodies.